Spikes in acute:chronic workload ratio (ACWR) associated with a 5–7 times greater injury rate in English Premier League football players: a comprehensive 3-year study. Issue 12 (21st February 2019) - Bowen, Laura; Gross, Aleksander Stephan; Gimpel, Mo; Bruce-Low, Stewart; Li, Francois-Xavier
Abstract : Objectives: We examined the relation between global positioning system (GPS)-derived workloads and injury in English Premier League football players (n=33) over three seasons. Methods: Workload and injury data were collected over three consecutive seasons. Cumulative (1-weekly, 2-weekly, 3-weekly and 4-weekly) loads in addition to acute:chronic workload ratios (ACWR) (acute workload (1-week workload)) divided by chronic workload (previous 4-week average acute workload) were classified into discrete ranges by z-scores. Relative risk (RR) for each range was then calculated between injured and non-injured players using specific GPS variables: total distance, low-intensity distance, high-speed running distance, sprint distance, accelerations and decelerations. Results: The greatest non-contact injury risk was when the chronic exposure to decelerations was low (<1731) and the ACWR was >2.0 (RR=6.7). Non-contact injury risk was also 5–6 times higher for accelerations and low-intensity distance when the chronic workloads were categorised as low and the ACWR was >2.0 (RR=5.4–6.6), compared with ACWRs below this. When all chronic workloads were included, an ACWR >2.0 was associated with a significant but lesser injury risk for the same metrics, plus total distance (RR=3.7–3.9). Conclusions: We recommend that practitioners involved in planning training for performance and injury prevention monitor the ACWR, increase chronic exposure to load and avoid spikes that approach or exceed 2.0.